The Influence of Mass Media, Family and Peers on Students’ Interest in Choosing the Pastry Field as a Career - Isa, Zainab Md; Saidin, Siti Salbiah; Jaafar, Normadiah; Abd Rahman, Reezlin (Advances in Social Sciences Research Journal, 2023)
Baling Community College is a Technical and Vocational Education and Training (TVET) institution playing a role in producing efficient and skilled workforces to contribute to the country’s development in fulfilling the needs of the current job market besides ensuring students are consistently competent in facing the challenges of the future job market. One of the career fields in demand is the pastry field which is offered at Baling Community College. This research was conducted to determine students’ interest in choosing the pastry field at Baling Community College to pursue their studies after completing their Sijil Peperiksaan Malaysia (SPM) as a future career path. The respondents from this research involved 60 students of Certificate in Pastry from Baling Community College through the use of the quantitative method. The research methodology was cross-sectional and the data analysis was conducted by using SPSS 26 (Statistical Package for the Social Sciences). In summary, the influences of mass media and family showed a relationship with students’ interest in choosing the pastry field. The results can help Baling Community College in highlighting the main criteria for boosting promotional activities to ensure intake norms of the pastry field reach the target.